Hepatorenal bypass as a salvage strategy after occlusion following branched endovascular aortic repair - Tainá Curado Gomes de Barros, MD; Dilson Pimentel, MS; Ana Beatriz Madeira Boffa, MD; Tayrine Mazotti de Moraes, MD; Grace Carvajal Mulatti, MD, PhD; Nelson De Luccia, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 63-year-old male patient with chronic dilated aortic dissection post-dissection aneurysm (maximum diameter, 110 mm) underwent staged endovascular surgical correction. Initially, thoracic endoprosthesis implantation was performed in 2020, with coverage of the proximal tear in the descending aorta. Later, in 2022, with the subsequent dilfation of the thoracoabdomial portion, a Cook TBranch endoprosthesis was implanted, using covered balloon-expandable stents for the visceral and the right renal artery. The left renal artery suffered a perforation in this procedure, and the branch was occluded with an Amplatzer plug. In 2024, he suddenly developed acute renal failure, requiring dialysis, and underwent a angiotomography computed tomography angiography that identified occlusion of the right renal branch. Renal scintigraphy confirmed the anatomical and functional viability of the right kidney. Subsequently, revascularization of the right renal artery was carried out by dissecting and distally sectioning it immediately after the occluded stent, followed by reimplantation into a branch of the right hepatic artery in a nearby location with an end-to-side anastomosis. The procedure was performed via xiphopubic laparotomy with superior rotation of the stomach and small intestine to the left. The patient progressed satisfactorily, exhibiting 800 mL of diuresis within the first 24 hours postoperatively, with progressive and gradual improvement in renal function and hypertension. At present, the patient remains independent of dialysis therapy.